2015
DOI: 10.3390/md13052967
|View full text |Cite
|
Sign up to set email alerts
|

Marine Polysaccharides from Algae with Potential Biomedical Applications

Abstract: There is a current tendency towards bioactive natural products with applications in various industries, such as pharmaceutical, biomedical, cosmetics and food. This has put some emphasis in research on marine organisms, including macroalgae and microalgae, among others. Polysaccharides with marine origin constitute one type of these biochemical compounds that have already proved to have several important properties, such as anticoagulant and/or antithrombotic, immunomodulatory ability, antitumor and cancer pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
273
0
14

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(291 citation statements)
references
References 383 publications
(387 reference statements)
4
273
0
14
Order By: Relevance
“…Related to skin ageing supplements and cosmeceutics, extracts from Chlorella vulgaris have been reported to support collagen repair mechanisms [31], and Raposo et al [45] reported that sulfated PS (sPS) produced and secreted by marine microalgae had shown the capacity to prevent the accumulation and activity of free radicals and reactive chemical species. Therefore, sPS might act as protecting systems against these oxidative and radical stress agents.…”
Section: Uses Of Microalgae and Cyanobacteria For Cosmetic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Related to skin ageing supplements and cosmeceutics, extracts from Chlorella vulgaris have been reported to support collagen repair mechanisms [31], and Raposo et al [45] reported that sulfated PS (sPS) produced and secreted by marine microalgae had shown the capacity to prevent the accumulation and activity of free radicals and reactive chemical species. Therefore, sPS might act as protecting systems against these oxidative and radical stress agents.…”
Section: Uses Of Microalgae and Cyanobacteria For Cosmetic Applicationsmentioning
confidence: 99%
“…The sPS from Porphyridium and Rhodella reticulate exhibited antioxidant activity that was dose-dependent. Methanolic extracts of exopolysaccharides (EPS) from A. platensis also exhibit a very high antioxidant capacity [45].…”
Section: Uses Of Microalgae and Cyanobacteria For Cosmetic Applicationsmentioning
confidence: 99%
“…Доказано, что зеленые водоросли Ulva и Caulerpa вырабатывают полисахариды, обладающие важными медицинскими качествами (Wang et al, 2014). Содержащиеся в их талломах сульфатированные полисахариды, в т. ч. S-галактаны, прояв-ляют различные терапевтические свойства, включая антиокисли-тельные (de Jesus Raposo et al, 2015). Оценка углеводного состава изученных видов позволит определить их пищевой и терапевтический потенциал.…”
Section: рис 2 общее количество углеводов в талломах водорослейunclassified
“…Marine polysaccharides can be employed as diluents/illers in the formulation of tablets (by all methods) to increase the mass of the solid dosage forms that hold a low concentration of therapeutic agent and thereby render the manufacturing process more reliable and reproducible [6]. For example, chitin and chitosan are used as a diluent or iller and as a binder in direct compression of tablet processing, as a disintegrant, and so on.…”
Section: As Diluentsmentioning
confidence: 99%